Water quality and distribution of Selorejo Reservoir using the Pollution Index, Oregon-WQI, and NSF-WQI methods - Ken Diah Mangar Nastiti; Rini Wahyu Sayekti; Emma Yuliani (Fakultas Teknik, Universitas Brawijaya, 2023)
Selorejo Reservoir is used for flood control activities, hydropower, agricultural irrigation, fisheries, and tourism. In 2021, the water quality of Selorejo Reservoir worsened, which was indicated by fish mortality and an increase of water lettuce plants; the decline in water quality of Selorejo Reservoir may be due to agricultural and farming waste that was carried by surface runoff and entered the reservoir. This study was conducted to determine the status of water quality in Selorejo Reservoir using the Pollution Index, Oregon-WQI, CCME-WQI, and NFS-WQI methods in the dry season based on the parameters of pH, BOD, COD, DO, TSS, Nitrates, Ammonia, Phosphate, and fecal coliform. Based on the Pollution Index method, the water quality was in the